Video Making Workshop by Linkages - Universiti Malaysia Sarawak, Institute of Social Informatics and Technological Innovations (Universiti Malaysia Sarawak (UNIMAS), 2014)
Workshop participated by PI1M Managers and Assistant Managers under UNIMAS